2022
DOI: 10.1002/ppul.26084
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial tuberculosis in children: Defining the role of interventional bronchoscopy

Abstract: Introduction: Endobronchial tuberculosis (EBTB) can lead to bronchopulmonary complications when diagnosis is delayed. Bronchoscopic treatment in children can be challenging due to small airway size. We report our experience treating children with EBTB.Methods: Retrospective study (2014−2020) of patients diagnosed with EBTB.Flexible bronchoscopy (FB) was performed in patients with previous diagnosis of pulmonary tuberculosis (PTB), after respiratory/radiological worsening was observed in spite of medical treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This procedure can be combined with cryoablation, electrocautery cuts followed by intralesional corticosteroid, or topical mitomycin-c application. 4 In our series, all four children with fibrostenosis underwent balloon dilatation, three in our institute and one elsewhere. Airway patency with just balloon dilatation was established only in a single child (25%).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…This procedure can be combined with cryoablation, electrocautery cuts followed by intralesional corticosteroid, or topical mitomycin-c application. 4 In our series, all four children with fibrostenosis underwent balloon dilatation, three in our institute and one elsewhere. Airway patency with just balloon dilatation was established only in a single child (25%).…”
mentioning
confidence: 76%
“…Data on interventions for pediatric EBTB are limited to case reports and small series. 3,4 Balloon dilatation is often the first intervention in patients with stenotic EBTB. In our Institute, we use a CRE balloon of appropriate size, inserted through the stenotic segment using a rigid bronchoscope.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also proven to be highly effective in the treatment of scarring central airway stenosis caused by bronchial tuberculosis. 5 , 9 The choice of thermal therapy for children is usually argon plasma coagulation (APC) which relies on argon gas to conduct an electrical current to perform non-contact coagulation to achieve a superficial necrosis effect on the target tissues. In the comparison of inflammatory and scar tissue formation responses to the use of cryoablation, APC, and radiofrequency, cryotherapy is reported to result in a significantly lower response of inflammation and scar tissue formation at the targeted sites in a mice experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Research reported the institution of interventional treatments such as balloon dilatation, thermal ablation, cryoablation, clamping, and stent placement, after half a month to one month of antituberculosis treatment, can reduce airway stenosis and pulmonary function damage in children. [7][8][9] Here we report a pediatric tuberculosis case complicated with benign stenosis of the central airway successfully managed with bronchoscopy balloon dilation with cryotherapy at an early anti-TB treatment phase.…”
Section: Introductionmentioning
confidence: 99%